Assessing the thermal stability of laser powder bed fused AlSi10Mg by short-period thermal exposure - Jie Wan; Huarui Geng; Biao Chen; Jianghua Shen; Katsuyoshi Kondoh; Jinshan Li (Virtual and Physical Prototyping, 2023)
Laser powder bed fused (LPBFed) AlSi10Mg is recognised for its superior mechanical properties. However, its thermal stability has never been justified. Herein, we exposed as-built AlSi10Mg to different temperatures (200–500°C) for only 3 min to evaluate its thermal stability. Results showed that LPBFed AlSi10Mg had relatively low thermal stability. Only 3 min of thermal exposure at 200°C would deteriorate its tensile strength dramatically. Microstructural analysis revealed that with increasing thermal input, as-built AlSi10Mg exhibited a microstructural evolution similar to annealing of cold-worked metals, namely recovery, recrystallisation followed by grain-growth. The excessive energy stored in as-built microstructure due to fast cooling during LPBF was deduced as the driving force for this phenomenon. Therefore, such microstructural change was at the expense of dislocations stored in the as-built material, which in turn caused deterioration in tensile strength. The present findings may provide guidance for the application of LPBFed AlSi10Mg.